Prospects of therapeutic action on FGFR signaling pathway - M. Yu. Fedyanin; D. N. Khmelkova; T. S. Serebriyskaya; T. A. Nikolskaya; S. A. Tyulyandin (Успехи молекулярной онкологии)
Fibroblast growth factors (FGFs) and their receptors (FGFRs) are involved in key cellular functions and cancerogenesis. Nowadays FGFR and their ligands are one of the most investigated markers in oncology and targets for specific therapy. There are a lot of clinical trials in on- cology include drugs with anti-FGFR activities. The most of these drugs are tyrosine kinase inhibitors and monoclonal antibodies. When we say about therapeutic effects on the FGFR signaling pathway, we say about opportunity not only block the ligands and FGFRs, but the under- lying molecular and signaling pathways activated by FGFRs. Nowadays the number of tyrosine kinase inhibitors selectively blocking FGFRs is extremely small. Typically, tyrosine kinase inhibitors can block a wide range of targets. Some of these inhibitors have entered in clinical practice in the treatment of metastatic tumors of different localizations, others are in clinical trials. On August 2014, 74 studies investigating inhibitors of FGFRs are registered on clinicaltrials.gov. A number of marketed drugs at high concentrations also has the ability to inhibit FGFR – sorafenib, vandetanib, motesanib, however, increasing the concentration of these drugs is associated with severe toxicity of treat- ment. In the recommended therapeutic concentrations, adequate blocking FGFR tyrosine kinase domain is doubtful. The review paid atten- tion to such drugs as pazopanib, nintedanib, cediranib, brivanib, dovitinib, ponatinib. We showed the results of treatment with inhibitors of FGFR in different cancers such as breast cancer, colon cancer, endometrial cancer, gastric cancer, thyroid cancer, lung cancer, ovarian cancer. Despite the fact that anti-FGFR therapy are at an early stage of clinical investigation, some difficulties in implementing this thera- peutic approach have been seen, such as high toxicity, not validated targets, the need for patient selection, depending on the activity of FGF– FGFR pathway, as well as mutations in genes of downstream molecular signaling pathways. In summary in the article we reviewed relevant literature to identify current status, difficulties and future perspectives in development of anti- FGFR drugs. In this article, we review FGFR signaling and describe the therapeutic intervention in patients with solid tumors.